Puerarin suppresses hypoxia-induced vascular endothelial growth factor upregulation in human retinal pigmented epithelial cells by blocking JAK2/STAT3 pathway. Issue 5 (2nd May 2022) - Tang, Huixin; Kong, Lingchun; Yang, Yuqin; Li, Jingjing; Zou, Hong
ABSTRACT: The purpose of this study was to explore the mechanism by which puerarin regulated the expression of hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) in humans' retinal pigment epithelial (RPE) cells under hypoxia. RPE cells (ARPE-19 and D407 cells) and a rat model of oxygen-induced retinopathy were used in the current study. Western blotting and ELISA were performed to detect the level of JAK2, phosphorylated JAK2, STAT3, phosphorylated STAT3, HIF-1α, and VEGF in cells. In addition, the interaction between JAK2 and STAT3 was determined using with a co-immunoprecipitation assay. We found puerarin inhibited hypoxia-induced upregulation of VEGF at both the mRNA and protein level via decreasing HIF-1α expression in RPE cells. Moreover, puerarin attenuated the interaction between JAK2 and STAT3, and subsequently blocking p-STAT3 nucleus translocation in vitro and in vivo . In conclusion, puerarin could effectively inhibit hypoxia-induced VEGF upregulation in RPE cells via mediated JAK2/STAT3 pathway. Graphical abstract: uf0001